Study on the Mechanism of Emotional Labor and Intellectual Thinking in Burnout - Zhao Jie (SHS Web of Conferences)
Research on the interaction mechanism of cognitive evaluation, intellectual thinking, and burnout syndrome generally refers to academic fields related to individual psychology and burnout, such as individual cognitive appraisal, intellectual thinking, emotional labor, and burnout. It is a general term for psychology and mental health, with an interdisciplinary and applied nature. Unlike a single discipline, it presents complex attributes. During the research, it is not easy to conduct in-depth research by quantifying or applying traditional psychological models, and the diversity of research methods is somewhat limited. With the emergence of big data and artificial intelligence, the academic community has been paying more and more attention to psychology research methods. In recent years, scientists have begun to pay attention to the combination of innovation and interdisciplinarity, and the construction and application of big data and artificial intelligence technologies in psychology is a typical example. Considering the complexity of the research objects and the problems involved, how to effectively integrate big data, artificial intelligence technology, and psychology has become a problem that needs to be solved urgently in academic circles. This study analyzes applying the above theories to practice to provide theoretical foundations and practical references for promoting the interface of internal and external elements and innovation in this field.